2018
DOI: 10.1186/s12245-018-0204-9
|View full text |Cite
|
Sign up to set email alerts
|

The feasibility of the 1-h high-sensitivity cardiac troponin T algorithm to rule-in and rule-out acute myocardial infarction in Thai emergency patients: an observational study

Abstract: BackgroundThe 3-h high-sensitivity cardiac troponin T (hs-cTnT) algorithm is the most commonly used scheme to diagnose acute myocardial infarction. The 1-h hs-cTnT algorithm has recently been approved by the European Society of Cardiology as an alternative algorithm for earlier diagnosis. If the hs-cTnT test cannot discriminate the diagnosis of the patient at 1 h, the patient is defined as observational group. Their test must be repeated at 3 h. A high prevalence of this group may indicate a low clinical utili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…After title and abstract screening, 54 studies were eligible for full-text review. After full-text review, a total of 15 studies were included for analysis(figure 1)6 7 9 14–16 28–36.…”
Section: Resultsmentioning
confidence: 99%
“…After title and abstract screening, 54 studies were eligible for full-text review. After full-text review, a total of 15 studies were included for analysis(figure 1)6 7 9 14–16 28–36.…”
Section: Resultsmentioning
confidence: 99%
“…Another trial aimed to investigate differences between a 0/3‐ and a 0/1‐hsTnt‐algorithm and found comparable performance. Noteworthy, the onset of chest pain was significantly different between the study groups 18 . Our results did not include a 0/1 hour‐algortithm, warranting future research.…”
Section: Discussionmentioning
confidence: 70%
“…Noteworthy, the onset of chest pain was significantly different between the study groups. 18 Our results did not include a 0/1 houralgortithm, warranting future research.…”
mentioning
confidence: 81%